Peran Sekolah dalam Mengembangkan Tingkat Kognitif Siswa Attention Deficit Hyperactivity Disorder (ADHD) di Skh Negeri 01 Kota Serang - sadiyah; Fauzi Fadliansyah; Anna Maria Oktaviani (Arus Jurnal Pendidikan, 2025)
This study aims to describe the role of schools in developing the cognitive abilities of students with Attention Deficit Hyperactivity Disorder (ADHD) at SKH Negeri 01 Kota Serang. This research employed a descriptive qualitative approach involving one ADHD student in Grade I, a classroom teacher, a special assistant teacher, and parents. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings reveal that schools play a crucial role in supporting the cognitive development of ADHD students through strategies such as seating arrangements to minimize distractions, short and repeated instructions, the use of visual learning media, scheduled breaks, and positive reinforcement in the form of praise and simple rewards. Hands-on activities and educational games were more effective in helping students understand the material. However, challenges remain in sustaining long-term concentration and managing impulsive behavior. In conclusion, the school’s role is vital in fostering the cognitive development of ADHD students, supported by collaboration with special assistant teachers and parents.